Music on Prescription to Aid Sleep Quality: A Literature Review - Dickson, Gaelen Thomas; Schubert, Emery (Frontiers in Psychology, 2020)
Investigations of music for improving sleep quality have produced mixed results. We investigated whether the number of music dosages could be a reason for the lack of clarity. Six longitudinal music sleep studies using the Pittsburgh Sleep Quality Index (PSQI) over three weeks were identified. Music was compared to active (audiobooks or medication) or passive controls, and significantly improved PSQI within the first or second week of prescription. PSQI improved with an average mean difference of -1.15 (SD = 0.53) for each week. Music continued to improve PSQI over a study that had a three-month music intervention (low score associated with better sleep). One study with a low initial PSQI score resulted in poor sleepers (PSQI>5) achieving healthy sleep (PSQI<5) within three weeks of regular music intervention. For future studies, ‘prescribing’ music beyond three weeks may lead to more instances of healthy sleep, particularly for those who have mild sleep problems. To explain the findings, we proposed that the relationship between weeks of music listening and improved PSQI are attributed to the truncation of poor bedtime habits linked to ruminative tendencies and consequent hyperarousal prior to the music intervention. Music listening at bedtime replaces those bad habits, we argue, by forming a new psychological link between bedtime and sleep through evaluative conditioning. The findings of the present study provide disarming evidence of the potential for prescription of music for treating mild sleep disorder.